Correlation between Family Support and Self Care in Type 2 Diabetes Mellitus: Meta-Analysis - Islami, Dian Dini; Tamtomo, Didik Gunawan; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Patients with Type 2 Diabetes Mellitus have a high risk of serious complications. Complications resulting from diabetes can be minimized and prevented by implementing self-care behavior. The study revealed that one of the factors that affect self-care activity is family support. The correlation of family support with self-care activity has been extensively investigated in several primary studies with several contradictions in the results. This study aimed to determine the correlation between family support and self-care activity in people with type 2 diabetes mellitus using the meta-analysis method.Subjects and Method: This study was a systematic review and meta-analysis. The meta-analysis was carried out by systematically reviewing articles published from 2010 to 2020 from the Pubmed, Google Scholar, DOAJ, and Springer Link databases using search keywords, namely (